PENGARUH TEKANAN REAKTOR PADA PENGHIDRORENGKAHAN TAR BATUBARA - Novie Ardhyarini; Daliya Indra Setiawan; Syntha Nardey (Research Center for Chemistry - LIPI, 2013)
Coal gasificationproduce tar as aside-product. Coal tar is a complexmixture, and consists of various functionalgroups mainly polyaromatic compounds.Due to its chemical composition, coal taris categorized as hazardous material. Thephysical and chemical properties of coaltar is similar to crude oil, but it has higherpolyaromatics and impurities. Thoseproblems are the main challenges ofprocessing coal tar into fuel. Therefore, anupgrading process is required This paperdiscussed upgrading coal tar into fuel byhydrocracking in an autoclave reactorusing catalyst of nickel-molybdenum withalumina-silica support. Effect of reactorpressure was observed Hydrocrackingproduct at 450Â°C and 120bar showed thebest result where the HIC molar ratioincreased 26% and the specijic gravitydecreased 19%. The impurities of sulphurand nitrogen decreased 88,5% and 72%respectively. Hydrocracking productwasdistilled using a simulated distillation bygas chromatography. Based on simulateddistillation analysis, the product could befractionated into 2,2%vol of light end,33.8%vol of naphtha, and 48%vol ofmiddle distillate. These results showed thatcoal tar is potential to be processed intofuel. Furthermore, the utilization of coaltar can be a solution of waste treatment aswell.Keywords :Coal tar, waste, hydro cracking,autoclave reactor, fuel